ANALISIS FAKTOR PENYEBAB TERJADINYA DUPLIKASI REKAM MEDIS ELEKTRONIK (RME) PADA SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DI RUMAH SAKIT AMC - Rahma Nisaa Ramadhani Kusetiono; Irda Sari (Jurnal Infokes, 2026)
This study aims to analyze the factors causing duplication of Electronic Medical Records in the Hospital Management Information System at AMC Hospital, which may affect both administrative and clinical service quality. The research employed a descriptive qualitative method through observation, interviews with five medical record officers, and document review related to patient index and SIMRS features. The main problem identified was the duplication of medical record numbers, with an average of five cases per month, influenced by the factors of Man, Machine, Method, Material, and Money. The findings show that patient misinformation, system weaknesses during data migration, rushed registration processes, incomplete patient identity data, and obstacles in BPJS claims are the dominant causes of duplication. Preventive efforts can be carried out by strengthening validation mechanisms based on the National Identification Number (NIK) integrated with BPJS data, improving patient education regarding the consistency of identity data, and proactively utilizing the “merge medical record” feature. This study recommends regular system evaluation and optimization of data validation mechanisms to improve the quality of EMR management in hospitals.